Assessment of Mastery Level of Effective Teaching Skills among Teachers in Inclusive Schools in Jordan - Lama Ghunaim (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
This study aims at evaluating the mastery level of effective teaching for teachers in inclusive schools in Jordan, and to investigate the differences in this level of mastery according to the variables of teacher qualification and experience. The study followed the descriptive survey approach, where the study sample consisted of (50) male and female teachers from the inclusive schools in Amman, and their teaching performance was observed using an observation card consisting of 38 phrases, distributed over three dimensions: planning, teaching and classroom management, and evaluation. The results indicated that the mean score of the teaching and classroom management dimension only was more than the assumed cutoff degree, and the difference between them is statistically significant at the level (α = 0.05), while there is no statistical significance for the rest of the dimensions means as well as for the total score. The findings also showed that there were statistically significant differences in the mastery of teaching with respect to specialization in favor of teachers majoring in education. Further, the findings showed that there were no statistically significant differences in the mastery of teaching due to experience. The study sheds light on the necessity of activating the role of educational supervision and training courses for in-service teachers, especially in the areas of planning and evaluation of the teaching-learning proces.